Turbulent Flow Around an Oscillating Body in Superfluid Helium: Dissipation Characteristics of the Nonlinear Regime - Zemma, E.; Luzuriaga, J. (Springer Nature, 2013)
Fil: Zemma, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina